APPEALING AGAINST JURY TRIALS - Gavrilov, Boris; Ilyukhov, Alexey; Perov, Anatoly; Kurpas, Marina (Revista Inclusiones, 2020)
The article examines the relevant issues of criminal proceedings considered in jury trials that are related to the appeal against verdicts delivered by a jury. The study considers different scientific opinions on the feasibility and effectiveness of appeals against verdicts delivered by a jury. In addition, it conducts a comparative-legal analysis in the framework of foreign law and a historical retrospective. While working on this article, the authors used the comparative-legal, historical, legal and statistical methods, as well as the method of systemic analysis. The study has concluded that the existing appeal model contradicts the institute of appeal correlating with cassation proceedings. Therefore, it is advisable to revise its legal nature and move from the model of "incomplete" appeal to a model in which a court of three professional judges forms a jury who will examine these factual circumstances again. The opposite verdict serves as the basis for repealing a sentence by a court of appeal. The procedure the authors have developed will strengthen the guarantees of individual rights in jury trials and reduce the prosecutorial bias in the Russian legal system. It is also necessary to compile a list of unconditional violations of criminal procedure law as the grounds for the remission or amendment of sentences by verdict.